2007
DOI: 10.1007/s10620-006-9672-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motilin and Mitemcinal (GM-611) on Gastrointestinal Contractile Activity in Rhesus Monkeys In Vivo and In Vitro

Abstract: Neither the presence of motilin receptors nor their action has been investigated in monkeys. The object of this study was to determine the effects of motilin and mitemcinal (GM-611), an erythromycin derivative, on the gastrointestinal tract in rhesus monkeys in vivo and in vitro. In in vivo investigations in conscious monkeys, both motilin and mitemcinal induced migrating motor complex-like contractions in the interdigestive state and also accelerated gastric emptying. In in vitro investigations, the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Since our earlier study showed that motilin and mitemcinal stimulated gastrointestinal contractions via motilin receptors in monkeys both in vivo and in vitro, as in humans [17], it can be assumed that mitemcinal accelerated gastric emptying in monkeys in the present study because its activity as a motilin agonist increased gastrointestinal contractile activity.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Since our earlier study showed that motilin and mitemcinal stimulated gastrointestinal contractions via motilin receptors in monkeys both in vivo and in vitro, as in humans [17], it can be assumed that mitemcinal accelerated gastric emptying in monkeys in the present study because its activity as a motilin agonist increased gastrointestinal contractile activity.…”
Section: Discussionmentioning
confidence: 52%
“…Our earlier study in Rhesus monkeys established that, unlike other commonly used animals, the in vitro and in vivo responses of Rhesus monkeys to motilin and motilin agonists (including mitemcinal) are similar to those seen in humans [17]. In the present study, therefore, we administered oral mitemcinal and three comparators (erythromycin, EM-574 [18] and cisapride) in conscious Rhesus monkeys and assessed and compared the effects of these drugs on gastric emptying, with the aim of investigating whether the effects of mitemcinal in monkeys would give further support to the hypothesis that mitemcinal has the potential to take the place of cisapride.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Mitemcinal has shown potent gastrointestinal motility-stimulating activity via motilin receptors in rabbits, dogs, and monkeys Ozaki et al 2007;Yogo et al 2007). In clinical studies, it has improved delayed gastric emptying (Fang et al 2004) and symptoms (McCallum and Cynshi 2007) in patients with diabetic gastroparesis.…”
Section: Introductionmentioning
confidence: 99%
“…1.; Koga et al, 1994). Mitemcinal has shown potent gastrointestinal motility-stimulating activity via motilin receptors in rabbits, dogs and monkeys Ozaki et al, 2007;Yogo et al, 2007). Cisapride, a piperidinyl benzamide prokinetic agent used for the treatment of gastrointestinal disorders, was withdrawn from the market in the United States in 2000 because of its propensity to prolong the QT interval, leading to lifethreatening TdP arrhythmias (Wysowski and Bacsanyi, 1996).…”
Section: Introductionmentioning
confidence: 99%